Pulling Together to Beat Superbugs Knowledge and Implementation Gaps in Addressing Antimicrobial Resistance - World Bank (World Bank, Washington, DC, 2019)
The rise of antimicrobial resistance (AMR), if not stopped, threatens to plunge humanity back into an era of health uncertainty few people alive today can remember. AMR does not follow national borders; its consequences affect the lives of everyone on the planet and blight the prospects of future generations. Yet with the right approach and intelligent investment, the AMR tide can be turned. Curbing the rise of AMR demands that it be refocused as a development problem. Addressing AMR is necessary to attain many of the sustainable development goals (SDGs), and it is likewise true that making progress on several SDGs and their specific targets also will contribute to tackling AMR. This virtuous synergy should be recognized more widely and exploited more fully.